Tawarruq As The Solution of Shariah Non Compliance in Ar-Rahn Practice: How Does It Work? - Qanita, Ariza; Meldona, Meldona; Wahyuni, Nanik (Review of Islamic Economics and Finance, 2024)
Purpose – This research aims to elaborate the concept of tawaruq as an alternative solution to the problem of sharia non-compliance in Rahn transactions in Indonesia. Many people are interested in Rahn transactions as financing that can help them to get their liquidity needs. However, in practice, rahn transactions are considered to contain elements of sharia non-compliance, namely taking ujrah based on the loan amount so that it is equated with usury.Methodology - This research used qualitative approach with literature review. The data used is secondary data in the form of journal articles, books and other documents published during the period 2015 to 2024.Findings - The research results show that the use of Tawarruq as a solution for sharia non-compliance in Rahn transactions is still controversial. There are scholars who consider it permissible and there are those who prohibit it. Tawarruq can be used as a solution in rahn transactions, but its implementation must be in accordance with predetermined limitations. DSN MUI as a fatwa institution in Indonesia should review the implementation of Tawarruq in sharia financial institutions, both legally and technically.